Surgical treatment associated with adjuvant chemotherapy with cyclophosphamide and piroxicam in cervical sarcoma of a blue-fronted amazon (Amazona aestiva): Case report - Barbosa, Bruna Emely Pereira; De Paiva, Felipe Noleto [UNESP]; Muzeti, Marcel Ricardo; Do Amaral, Raissa Garib Pacheco (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2021)
The occurrence of neoplasms in birds is still unknown, with the literature based mainly on scarce reports, in this context, data about epidemiology in specific species are almost nonexistent. Sarcomas are malignant mesenchymal origin neoplasms, which can develop from different tissues, such as adipose, cartilage, bone, among others. The occurrence of sarcomas in birds has been previously described, with different therapeutic approaches. The present report describes the clinical approach in a blue-fronted amazon (Amazona aestiva) diagnosed with a soft tissue sarcoma in the dorsal cervical region, with surgical excision associated with a metronomic chemotherapy protocol as an adjuvant. The therapeutic combination proved to be effective in controlling the disease, guaranteeing important survival, with clinical absence of side effects.
Tratamento cirúrgico com uso de quimioterapia adjuvante com ciclofosfamida e piroxicam em sarcoma cervical de um papagaio-verdadeiro (Amazona aestiva): Relato de caso
Keywords: Histopathology; Neoplasm; Oncology; Parrots; Wild birds